2014
DOI: 10.1115/1.4027612
|View full text |Cite|
|
Sign up to set email alerts
|

A Computational Method for Predicting Inferior Vena Cava Filter Performance on a Patient-Specific Basis

Abstract: A computational methodology for simulating virtual inferior vena cava (IVC) filter placement and IVC hemodynamics was developed and demonstrated in two patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…1,7 The veins were modelled as anisotropic, hyperelastic material using the Holzapfel-Gasser-Ogden (HGO) formulation. 2,9,13 Local material directions were assigned to the veins using a cylindrical coordinate system. Since the actual material properties were unknown, average values were obtained on the tensile properties of human IVCs from a published work 26 and fitted to the HGO model to obtain the stressstretch curves.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…1,7 The veins were modelled as anisotropic, hyperelastic material using the Holzapfel-Gasser-Ogden (HGO) formulation. 2,9,13 Local material directions were assigned to the veins using a cylindrical coordinate system. Since the actual material properties were unknown, average values were obtained on the tensile properties of human IVCs from a published work 26 and fitted to the HGO model to obtain the stressstretch curves.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Though blood is a non-Newtonian fluid, (1) showed that the Newtonian approximation introduces less than 10% error in velocities when simulating flow in a simplified IVC geometry (5). The density of the fluid was 1.07g/cm 3 and its viscosity was 0.041g/cms.…”
Section: Fsi Model Properties and Boundary Conditionsmentioning
confidence: 99%
“…Previous experimental and computational studies have investigated the hemodynamic effects of IVC filter placement and embulus capture rate in simplified IVC geometries (5). Many in vitro studies have been performed using optical methods such as particle imagine velocimetry (6; 7; 8; 9; 10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most of these works are related only to clinical results or fluid analyses, without addressing the improvement of filter design. While there have been several hemodynamic studies of IVC filters, fewer have been published on the mechanical interaction between the vena cava and metallic filter …”
Section: Introductionmentioning
confidence: 99%
“…While there have been several hemodynamic studies of IVC filters, 4,[19][20][21][22][23][24][25][26][27] fewer have been published on the mechanical interaction between the vena cava and metallic filter. [28][29][30] Analysis of other aspects of filter design such as strut perforation or filter migration are needed to evaluate the effectiveness of filters and develop new device models. In a previous study, García et al 28 evaluated the extraction forces and stress at the end of the struts by an experimental setup and a finite element (FE) simulation without an analysis of the interaction forces between the metallic strut and vena cava tissue.…”
Section: Introductionmentioning
confidence: 99%